2022
DOI: 10.1021/acs.jproteome.1c00786
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Snapshot of Plasma Samples Reveals New Pathways Implicated in SARS-CoV-2 Pathogenesis

Abstract: Despite the scientific and human efforts to understand COVID-19, there are questions still unanswered. Variations in the metabolic reaction to SARS-CoV-2 infection could explain the striking differences in the susceptibility to infection and the risk of severe disease. Here, we used untargeted metabolomics to examine novel metabolic pathways related to SARS-CoV-2 susceptibility and COVID-19 clinical severity using capillary electrophoresis coupled to a time-of-flight mass spectrometer (CE-TOF-MS) in plasma sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…In an early study, Danlos et al (2021) investigated plasma samples from a well-stratified cohort of COVID-19 patients to identify up to 77 metabolites (amino acids, polyamines, sugars and their derivatives among others) that differ between critical and mild patients. These results were further confirmed and extended by subsequent studies in plasma as well ( Albóniga et al, 2022 ; Dillard et al, 2022 ), using other matrices ( Buyukozkan et al, 2022 ; Dewulf et al, 2022 ) or as a part of a multi-omic study ( Su et al, 2020 ; Wu et al, 2021 ). All these contributions highlight the critical role that kynerurate pathway has in the metabotype associated to the disease severity ( D’Amora et al, 2021 ; Marín-Corral et al, 2021 ; Roberts et al, 2022 ).…”
Section: Biomarkers Of Covid-19 Severitysupporting
confidence: 69%
See 1 more Smart Citation
“…In an early study, Danlos et al (2021) investigated plasma samples from a well-stratified cohort of COVID-19 patients to identify up to 77 metabolites (amino acids, polyamines, sugars and their derivatives among others) that differ between critical and mild patients. These results were further confirmed and extended by subsequent studies in plasma as well ( Albóniga et al, 2022 ; Dillard et al, 2022 ), using other matrices ( Buyukozkan et al, 2022 ; Dewulf et al, 2022 ) or as a part of a multi-omic study ( Su et al, 2020 ; Wu et al, 2021 ). All these contributions highlight the critical role that kynerurate pathway has in the metabotype associated to the disease severity ( D’Amora et al, 2021 ; Marín-Corral et al, 2021 ; Roberts et al, 2022 ).…”
Section: Biomarkers Of Covid-19 Severitysupporting
confidence: 69%
“…Tryptophan is an essential amino acid and a neurotransmitter, and with phenylalanine also involved in the modulation of the immune response ( Fernstrom and Wurtman, 1971 ) and inflammatory processes in lung and kidney diseases, or other infections like HIV or sepsis ( Darcy et al, 2011 ; Kimhofer et al, 2020 ). SARS-CoV-2 infection also alters many other metabolic pathways ( Albóniga et al, 2022 ), with changes in the serum amino acid signature (for instance, elevated glutamine/glutamate and Fischer’s ratios) ( Doğan et al, 2021 ; Páez-Franco et al, 2022 ). Glutamate alteration in COVID-19 is in part mediated by the α-glutathione S-transferase, associated with certain processes such as liver failure, skeletal muscle metabolism, cancer or immunodeficiency ( Kinscherf et al, 1996 ; Cruzat et al, 2018 ).…”
Section: Metabolic Signature Of the Acute Phase Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Metabolic snapshot of COVID-19 revealed some additional interconnection pathways implicated in disease pathogenesis, including citrulline, phenylalanine and histidine, 2-aminobutyric acid, asymmetric dimethylarginine. 605 The disordered metabolic pathways of primary Sjögren’s syndrome patients are associated with tyrosine metabolism, tryptophan metabolism, aspartate and asparagine metabolism, carbon fixation and affect neurological cognitive impairment, inflammatory injury, and the immune response. 606 Pathway analysis by urinary metabolomic study demonstrated that aberrant metabolisms involved in aspartate metabolism, glycine metabolism, glycolysis, glyoxylate metabolism, and TCA cycle.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Untargeted metabolomics can reveal important biological associations in immunology research and identify novel metabolites/biomarkers specific to a disease (Ding et al , 2021b ; Alboniga et al , 2022 ; Aximujiang et al , 2022 ; Chen et al , 2022 ; Tian et al , 2022 ). For example, Zhu et al ( 2022 ) used high‐resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa.…”
Section: Targeted and Untargeted Metabolomics For Immunology Researchmentioning
confidence: 99%
“…This approach is currently widely used in the discovery of biomarkers, disease diagnosis, and mechanism research, and it provides new insights into the complex study of disease mechanisms (Haimerl et al, 2021;Krishnan et al, 2021;Roberts et al, 2021;Choueiry et al, 2022). Untargeted metabolomics can reveal important biological associations in immunology research and identify novel metabolites/biomarkers specific to a disease (Ding et al, 2021b;Alboniga et al, 2022;Aximujiang et al, 2022;Chen et al, 2022;Tian et al, 2022). For example, Zhu et al (2022) used high-resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa.…”
Section: Untargeted Metabolomicsmentioning
confidence: 99%